Análisis del servicio de atención al usuario que brinda el infocentro del GAD La Maná, año 2015 - Tubón Macías, Mayra Maricela (2016)
The current research project was carried out in the Canton the Mana province of Cotopaxi having as main objective the "analysis of the service to the user who provides the databank of the Mana Gad, year 2015." The problem focuses on attention to the user who provides the databank which according to users does not respond adequately to the requirements that apply when they come to this institution for this reason, it is necessary to research staff who is in charge of the user services. The methodology used for this research is qualitative methods of research as inductive method were used deductive, analytical and synthetic to gather information techniques were applied as the interview to the head of this institution and 327encuesta students of the different educational institutions, the results were analyzed by applying statistical graphics and pictures. The obtained results we can highlight responses mostly personnel working in the infocentro unknown plans to improve the care and services to the customer, there is difficulty in the digital system and this delay processes, solutions is taken for this ranging from training, motivation and commitment to the function and the service that gives users the infocentro. Through surveys, it was determined that there is dissatisfaction of the users with regard to care and services Besides analysis allowed to know that the effort is aimed at compromise with the user. However, there are obvious traits of weakness by this institution that must be corrected.